Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5ra10067d
|View full text |Cite
|
Sign up to set email alerts
|

Improved stability and enhanced efficiency of dye sensitized solar cells by using europium doped yttrium vanadate down-shifting nanophosphor

Abstract: Through detailed experiments, it has been deduced that ultraviolet (UV) light is a major factor in the degradation of dye-sensitized solar cell (DSSC) performance due to generation of surface defects in nanoporous TiO 2 and dye structural modification with free radical formation. We describe a simple spray deposition method to coat europium doped yttrium vanadate (YVO 4 :Eu 3+ ) down-shifting (DS) phosphor nanoparticles (NPs) on the front side of DSSCs in order to enhance photocurrent and mitigate UV induced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“… By promoting the use of different materials in the manufacture of electrodes like nanotubes, nanowires of carbon, graphene; using varied electrolytes instead of a liquid one like gel electrolyte and quasi-solid electrolytes; providing different pre-post treatments to the working electrode like anodization pre-treatment and TiCl 4 treatment; using different types of CEs [ 14 ] and by developing hydrophobic sensitizers, the performance as well as the efficiency of these cells can be tremendously improved. By inserting phosphorescence or luminescent chromophores, such as applying rare-earth doped oxides into the DSSC [ 58 – 60 ], coating a luminescent layer on the glass of the photoanode [ 60 62 ], i.e., using plasmonic phenomenon [ 63 ] and adding energy relay dyes (ERDs) to the electrolyte [ 57 , 64 , 65 ]. …”
Section: Different Ways To Augment the Efficiency Of Dsscsmentioning
confidence: 99%
“… By promoting the use of different materials in the manufacture of electrodes like nanotubes, nanowires of carbon, graphene; using varied electrolytes instead of a liquid one like gel electrolyte and quasi-solid electrolytes; providing different pre-post treatments to the working electrode like anodization pre-treatment and TiCl 4 treatment; using different types of CEs [ 14 ] and by developing hydrophobic sensitizers, the performance as well as the efficiency of these cells can be tremendously improved. By inserting phosphorescence or luminescent chromophores, such as applying rare-earth doped oxides into the DSSC [ 58 – 60 ], coating a luminescent layer on the glass of the photoanode [ 60 62 ], i.e., using plasmonic phenomenon [ 63 ] and adding energy relay dyes (ERDs) to the electrolyte [ 57 , 64 , 65 ]. …”
Section: Different Ways To Augment the Efficiency Of Dsscsmentioning
confidence: 99%
“…Accordingly, N. Chander group demonstrated Eu 3 + : YVO 4 phosphor nanoparticles (NPs) as down-shifting (DS) layer deposited via spray coating on the front side of DSC to prevent the device degradation from UV rays and enhance the performance of device. [101] These phosphors exhibited a broad absorption which increases the absorption of the dyes further increasing the J sc shown in Figure 10(a). DSC test cells with phosphor layer are stable even after 26 days is represented in Figure 10 [102] In an another study, Vinod kumar et al, reported Eu doped TiO 2 downshifting layered based DSC which shows higher J SC due to the rise in the number of photons in the visible region…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 95%
“…These phosphors absorb UV light and converts to visible light, harvesting more sunlight that increases J sc of the DSC. Accordingly, N. Chander group demonstrated Eu 3+ : YVO 4 phosphor nanoparticles (NPs) as down‐shifting (DS) layer deposited via spray coating on the front side of DSC to prevent the device degradation from UV rays and enhance the performance of device . These phosphors exhibited a broad absorption which increases the absorption of the dyes further increasing the J sc shown in Figure (a).…”
Section: Dc/uc Phosphors For Dsc/psc Applicationsmentioning
confidence: 99%
“…for most laboratories because of the aforesaid reasons [11][12][13][14]. Despite of high efficiency in DSSC, the commercialization of the same has been hindered due to the chief issues related to instability-factor, leakage of liquid electrolytes etc.…”
Section: Introductionmentioning
confidence: 99%